Business Development Strategy for Coffee Agroindustry Using Analytical Hierarchy Process and Quantitative Strategic Planning Matrix Methods - Liasanta Tarigan; Devi Maulida Rahmah (Agroindustrial Technology Journal, 2025)
Coffee is one of Indonesia's leading commodities, particularly in West Java. However, smallholder coffee enterprises such as Koffie Tandjoeng and Kopi Buhoen in Sumedang face several challenges, including decreased production due to climate factors, competition for raw materials, and limited marketing strategies. This study aims to formulate development strategies for smallholder coffee businesses by using the SWOT method to identify internal strengths and weaknesses, as well as external opportunities and threats, and the AHP and QSPM methods to determine the most appropriate strategies. The results show that the main strategy for Koffie Tandjoeng is to develop premium products and expand into the hotel and restaurant sectors. Meanwhile, Kopi Buhoen is advised to strengthen partnerships to ensure a stable supply of raw materials. The implementation of these strategies is expected to enhance the competitiveness and sustainability of smallholder coffee businesses in Sumedang.